Deaths from depressive events in women in Brazil in the last decade (Research, Society and Development, 2022)
Depression is a disease of a pandemic character, rapidly increasing in the population, which requires more studies, especially in women, in view of its physiological, social and neuroendocrinological transfigurations that predispose to mood disorders. The objective of this study was to study the epidemiological profile of deaths from depressive disorders in women in Brazil in the last decade. An epidemiological study was carried out, with a time series (2010 to 2019), with data collection from the SUS Information System (TABNET-DATASUS), exported to Excel and the Bioestat 5.3 Program and presented their absolute numbers and descriptive statistics. There were 3,155 deaths from depressive events in women. In 2014 (n=253) deaths, distributed in an increasing way and in 2019 (n=365). Regarding the Brazilian Region, deaths from depressive events in women were distributed as follows: Southeast (n=1845 cases), Northeast (n=1723 cases), South (n=1137 cases), Midwest (n=311 cases) and North(n=228). As for age groups: 80 or more was most affected with 27%. As for race: white women (n =1765), brown (n=1012) and black women (n=213). Regarding marital status, there was a greater number of deaths among widows 31%. About the place of occurrence: home environment (n=1769), hospital environment (n=1072). Regarding the ICD-10 category: depressive episodes (n=2758) and recurrent depressive disorders (n=397). Given this profile, the aim is to provide subsidies for managers to improve the implementation of public policies for greater prevention and for the treatment of women who present these depressive events, in addition to disseminating the discussion on the subject and contributing to academic knowledge in the research on depression in women, in order to reduce such deaths.